2018
DOI: 10.1016/j.tcr.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Serious phlegmonous lesion of the hand following an injury by vegetal thorn: Never forget Pasteurella multocida !

Abstract: Pasteurella multocida can cause serious infections after dog or cat bite. We report here a rare case of hand infection caused by P. multocida consecutive to an injury by a thorn of the prickly pear. It caused an amputation of the distal phalanx of the thumb in a trisomic patient.It is about a 27-year-old man who was admitted to the hospital with swelling and intense pain of the left hand. He reported a sting by a thorn of prickly pear 15 days before. The patient was admitted to proceed with operative irrigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Pasteurella multocida isolates are generally classified into five capsular types (A, B, D, E, and F) [1], and are commonly associated with respiratory diseases and hemorrhagic septicemia in a wide range of domestic and wild animals [2]. While it rarely occurs, P. multocida infections in humans have been continuously reported [3,4,5,6,7], and most of these cases are likely to be transmitted from pets such as dogs and cats [4,8]. It has been reported that the infection of P. multocida isolates displays host predilection; different capsular types are associated with specific types of diseases [2,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Pasteurella multocida isolates are generally classified into five capsular types (A, B, D, E, and F) [1], and are commonly associated with respiratory diseases and hemorrhagic septicemia in a wide range of domestic and wild animals [2]. While it rarely occurs, P. multocida infections in humans have been continuously reported [3,4,5,6,7], and most of these cases are likely to be transmitted from pets such as dogs and cats [4,8]. It has been reported that the infection of P. multocida isolates displays host predilection; different capsular types are associated with specific types of diseases [2,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Gram staining is negative and bipolar staining is common. These bacteria are immobile and they do not form endospores [ 1 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms are often accompanied by lymphangitis and satellite lymphadenopathy. In the absence of treatment, subacute forms can lead to arthritis and phlegmons of sheaths [ 1 , 9 ]. Respiratory infections occur in cases of immunosuppression, ethylic, smoking, bronchial dilation, and cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations